Sexual minority and depression: The moderating role of parental support - Þórdís Gísladóttir 1991- (2015)
The aim of the study was to examine whether parental support buffered the effects of same sex sexual attraction on depressed mood. A random sample of 2040 participants was drawn from the population-wide cross-sectional data from the 2013 Youth in Iceland study. The participants were high school students aged 16-20 years. Using univariate analysis of variance (ANOVA), the study examined whether belonging to a sexual minority group increased depression, whether parental support decreased the likelihood of depression and finally whether the effect of belonging to a sexual minority group on depression were stronger when parental support was low than when it was high. The results indicated that those reported having average or great sexual attraction to the same sex, had higher mean levels of depression than those who reported not being sexually attracted to the same sex. Parental support moderated depression among adolescents regardless of sexual attraction. Finally, new information was found regarding the group who reported having average sexual attraction to the same sex. Those belonging to that group seemed to be worse off in depression scores when parental support was low as well as when support was high, but when support increased a little, a steep decline was found in depression scores. Keywords: Same-sex sexual attraction, depression, parental support, sexual minority Markmið rannsóknarinnar var að kanna hvort stuðningur foreldra hefði áhrif á þunglyndi þeirra unglinga sem laðast kynferðislega að sama kyni. Í rannsókninni voru notuð fyrirliggjandi gögn frá Rannsóknum og greiningu úr þýðisrannsókn þeirra ,,Ungt fólk” frá 2013. Tilviljunarkennt úrtak sem samanstóð af 2040 þátttakendum var fengið og voru það nemendur í framhaldsskóla á aldrinum 16-20 ára. Rannsóknin kannaði hvort að það, að tilheyra minnihlutahópi hvað varðar kynhneigð yki líkur á þunglyndi, hvort að stuðningur foreldra minnkaði líkur á þunglyndi og hvort á áhrif þess að tilheyra minnihlutahóp hvað varðar kynhneigð á þunglyndi væru sterkari ...